Analysis of Non-Medical Logistics Management in the Equipment and Household Sub-Division of Bangkinang Hospital in 2023 - Nelly Tawarma*; Hastuti Marlina (Riwayat: Educational Journal of History and Humanities, 2023)
Non-medical logistics management is an important aspect in supporting hospital services. Bangkinang General Hospital as a regional referral hospital in Kampar District has carried out non-medical logistics management in the equipment and household sub-section. Even, the management of non-medical logistics at Bangkinang General Hospital has not yet reached the 100% SPM target. The aim of the study was to obtain in-depth information about the analysis of non-medical logistics management in the household and equipment sub-section of Bangkinang General Hospital in 2023. This type of research is qualitative with a phenomenological approach. There were 13 informants consisting of heads and staff of asset management installations, logistics management, non-medical logistics installations, equipment and household divisions, service unit users, outpatient and inpatient care. The triangulation used is source, method and data triangulation. The results showed that the 7 functions of non-medical logistics management, namely planning and determining needs, budgeting, procurement, receiving, storage and distribution, maintenance, elimination and control have not been carried out efficiently and effectively because forecasting methods, lead time, safety stock and reorder points have not been implemented. well, there are budget constraints to accommodate needs, storage and distribution do not use the FIFO and FEFO principles, there are stockouts and overstocks and non-medical logistics management in 2022 has not yet reached the SPM, namely the timeliness of picking up goods is only 97.5%, the achievement of picking up goods is 33 minutes, the maintenance time for non-medical logistics has only reached 90%. Regent of Kampar Regency, relevant SKPD and SKPKD can formulate new regulations regarding technical requirements for hospital non-medical logistics management including technical requirements for non-medical logistics warehouse buildings and infrastructure